Pengaruh Kompetensi SDM Terhadap Kualitas Laporan Keuangan Pemerintah Dengan Intervening Pencegahan Fraud - Sahmin Noholo (Program Studi S1 Akuntansi Jurusan Akuntansi, Fakultas Ekonomi Universitas Negeri Gorontalo, 2021)
This study aims to determine the effect of human resource competence on the quality of government financial reports with fraud prevention as an intervening variable. The approach in this research is quantitative with the expost facto method. The data in this study are primary data through a questionnaire. The data analysis used is descriptive analysis and inferential analysis (SEM PLS). The results of this study indicate that (1) Human Resource Competence has a positive but not significant effect on Fraud Prevention. (2) Human Resource Competence has a positive and significant impact on the Quality of Government Financial Reports. (3) Fraud Prevention has a positive and significant effect on the Quality of Government Financial Reports. (4) Competence of Human Resources through Fraud Prevention has a positive but not significant effect on the Quality of Government Financial Reports.